1986
DOI: 10.1139/v86-259
|View full text |Cite
|
Sign up to set email alerts
|

Open chain nitrogen compounds. Part XI. 3,7-Bis(arylazo)-1,3,5,7-tetraazabicyclo[3,3,1]nonanes: the reaction of diazonium ions with ammonia–formaldehyde mixtures

Abstract: Reaction of a series of diazonium salts with either hexamine or an aqueous mixture of ammonia–formaldehyde affords 3,7-bis(arylazo)-1,3,5,7-tetraazabicyclo[3,3,1]nonanes; several new examples of this novel class of bicycloheterocycle have been prepared and characterized. Analysis of the low-temperature nmr spectra of one compound in this series shows that the bicyclic system prefers the chair–chair conformation. The bis(arylazo)tetraazabicyclononanes, which are surprisingly stable in aqueous buffer compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…1,3,6,8-Tetraazatricyclo[4.4.1.1 3,8 ]dodecane ( 7 ) has been shown via X-ray crystal structure to be the condensation product of ethylenediamine with formaldehyde in the solid state. Therefore, the reaction mechanism for the formation of 3,8-di[2-aryl-1-azenyl]-1,3,6,8-tetraazabicyclo[4.4.1]undecanes is believed to be the route shown in Scheme , which is analogous to the mechanism for bis(arylazo)tetraazabicyclononane ( 3 ) formation previously reported . Supporting evidence for the mechanism in Scheme is the fact that direct diazonium coupling with the dodecane ( 7 ) results in a higher yield of 6 .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…1,3,6,8-Tetraazatricyclo[4.4.1.1 3,8 ]dodecane ( 7 ) has been shown via X-ray crystal structure to be the condensation product of ethylenediamine with formaldehyde in the solid state. Therefore, the reaction mechanism for the formation of 3,8-di[2-aryl-1-azenyl]-1,3,6,8-tetraazabicyclo[4.4.1]undecanes is believed to be the route shown in Scheme , which is analogous to the mechanism for bis(arylazo)tetraazabicyclononane ( 3 ) formation previously reported . Supporting evidence for the mechanism in Scheme is the fact that direct diazonium coupling with the dodecane ( 7 ) results in a higher yield of 6 .…”
Section: Discussionmentioning
confidence: 52%
“…For example, reaction of the diazide N 3 CH 2 CH 2 N 3 with an alkyllithium reagent affords 1,2-bis(alkyltriazeno)ethanes (1), which are potently cytotoxic due possibly to their ability to cross-link DNA . Under appropriate conditions, the reaction of a diazonium salt with a mixture of methylamine and formaldehyde affords the bis(triazenyl)methylamine ( 2 ), whereas similar diazonium coupling with a mixture of formaldehyde and ammonia produces the bis (triazenyl)tetraazabicyclononane ( 3 ) …”
Section: Introductionmentioning
confidence: 99%
“…Recrystallization of some of the triazinols from solvent mixtures containing methanol frequently resulted in failure to recover the Chydroxytriazine and it became apparent that the carbinolamines were undergoing methanolysis to give new products, the 4-methoxytriazines (14)(15)(16)(17)(18)(19)(20). When this methanolysis was studied in pure methanol, it was found that the reaction can give virtually quantitative yields of the methyl ethers and also that the rate of reaction is strongly dependent on the nature of the substituents R' and R~.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear magnetic resonance spectra of these novel cyclic carbinolamines suggest that they exist in equili-'For part XI, see ref. 15. '~uthor to whom all correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Hexamethylenetetramine is known to react with diazonium salts to form a diazononane derivative. [22][23][24] Use of diazotised groups commonly used for surface adsorption such as benzotriazole 25 and hydroxyquinoline 20 appeared to give small amounts of the desired product but were difficult to isolate and † Electronic supplementary information (ESI) available: full experimental details on the synthesis and analysis of the reported compounds. See http:// www.rsc.org/suppdata/cc/b2/b207885f/ characterize.…”
mentioning
confidence: 99%